Elements of information theory - Cover, Thomas M. (John Wiley y Sons, 2006)
The latest edition of this classic is updated with new systems and materials problems The second edition of this book maintains the tradition fundamental text book clear instructions, reflection. Readers are provided once again with an instructive mix of mathematics, physics, statistics and information theory. All the essential topics of information theory are covered in detail, including entropy, data compression, channel capacity, rate distortion theory of network information, and hypothesis testing. The authors provide readers with a solid understanding of the underlying theory and applications. Problem sets and a telegraphic summary at the end of each chapter further assist readers. The historical notes that follow each chapter summarizes the main points. The second edition includes: * Chapters reorganized to improve teaching * 200 new problems * New material on source coding, portfolio theory, and feedback capacity * Updated references Now current and enhanced, the Second Edition of Elements the information theory book remains ideal for upper-level undergraduate and graduate courses in electrical engineering, statistics and telecommunications text.